T helper type 17 in psoriasis: From basic immunology to clinical practice - Hsien-Yi Chiu; Yu-Pin Cheng; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2012)
Psoriasis is a chronic inflammatory disease mediated by a complex interplay between immune system and keratinocytes. Initially considered as a keratinocyte proliferation/differentiation disorder, an immune dysregulation was confirmed after the successful treatment of psoriasis with cyclosporine. The ying-yang theory, or T helper type 1 (Th1)/Th2 concept, was then introduced to explain the rarity of atopic dermatitis in patients with psoriasis and the aggravation of psoriasis after interferon-γ treatment. However, recent advances have revised the Th1/Th2 paradigm after the discovery of a novel subset of T cells, called Th17 cells. Th17 cells produce interleukin (IL)-17 and IL-22, and have other important downstream proinflammatory effects on skin, leading to clinical and pathological features typical of psoriasis. Nowadays, emerging evidence suggests integrative and complicated inflammatory circuits among Th1 and Th17 cells and keratinocytes in the pathogenesis of psoriasis, with Th17 cells playing a central role. Herein, we review the biology of Th17 cells as well as the reciprocal interplay between Th17 and regulatory T cells in psoriasis. Integration of the IL-23/Th17 axis into a revised concept of psoriasis has already been translated into novel therapeutic strategies. Studies investigating the effect and molecular mechanism of conventional and biological therapy for psoriasis on the IL-23/Th17 pathway were also discussed.